Non HIV antivirals - Klotman, Mary (Henry Stewart Talks, 2007)
Pharmacokinetics and clinical application of antiviral agents excluding antiretrovirals for HIV, The therapeutic and prophylactic options for herpes infections including herpes simplex 1 and 2, varicella zoster and cytomegalovirus, Therapeutic and prophylactic agents for influenza, Approved agents for the treatment of hepatitis B and C
Archived at 2018/03/15